The Efficacy and Safety of Pulmonary Vasodilators in Pediatric Pulmonary Hypertension (PH): A Systematic Review and Meta-analysis - Shu, Tingting; Chen, Huaqiao; Wang, Lu; Wang, Wuwan; Feng, Panpan; Xiang, Rui; Wen, Li; Huang, Wei (Frontiers in Pharmacology, 2021)
Background: We performed a meta-analysis to evaluate the efficacy and safety of pulmonary vasodilators in pediatric pulmonary hypertension (PH) patients. Methods: We searched electronic databases including PubMed, EMBASE, and the Cochrane Library up to May 2020, and conducted a subgroup analysis for pulmonary vasodilators or underlying disease. Results: Fifteen studies with 719 pediatric PH patients were included in the meta-analysis. Adverse events did not differ (P = 0.11, I2 = 15%) between the pulmonary vasodilators group and the control group, neither in the subgroups. In total, compared with the control group treatment, pulmonary vasodilators significantly decreased the mortality (P = 0.002), mean pulmonary artery pressure (mPAP, P = 0.02), and mechanical ventilation duration (P = 0.03), also improved the oxygenation index (OI, P = 0.01). In the persistent pulmonary hypertension of the newborn (PPHN) subgroup, phosphodiesterase type 5 inhibitors (PDE5i) significantly reduced mortality (P = 0.03), OI (P = 0.007) and mechanical ventilation duration (P = 0.004). Administration of endothelin receptor antagonists (ERAs) improved OI (P = 0.04) and mechanical ventilation duration (P < 0.00001) in PPHN. We also found that in the pediatric pulmonary arterial hypertension (PPAH) subgroup, mPAP was pronouncedly declined with ERAs (P = 0.006). Systolic pulmonary artery pressure (sPAP, P < 0.0001) and pulmonary arterial/aortic pressure (P < 0.00001) were significantly relieved with PDE5i, partial pressure of arterial oxygen (PaO2) was improved with prostacyclin in postoperative PH (POPH) subgroup (P = 0.001). Compared with the control group, pulmonary vasodilators could significantly decrease PA/AO pressure (P < 0.00001) and OI (P < 0.00001) in the short-term (duration < 7 days) follow-up subgroup, improve mPAP (P = 0.03) and PaO2 (P = 0.01) in the mid-term (7 - 30 days) follow-up subgroup, also decrease mortality, mPAP (P = 0.0001), PA/AO pressure (P = 0.0007), duration of mechanical ventilation (P = 0.004), and ICU stay (P < 0.00001) in the long-term follow subgroup (> 30 days). Conclusions: Pulmonary vasodilators decrease the mortality in pediatric PH patients, improve the respiratory and hemodynamic parameters, reduce the mechanical ventilation duration.